Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1097/01.pra.0000422739.49377.17
|View full text |Cite
|
Sign up to set email alerts
|

“What’s in a Name?” Delirium by Any Other Name Would Be as Deadly. A Review of the Nature of Delirium Consultations

Abstract: This study highlights the need for educational programs and easy to implement screening tools to ensure delirium is not overlooked.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…The individual is, therefore, likely to have reduced orientation to their environment, and at times to oneself. This symptom has sometimes been referred to as 'reduced level of conscious ness' or confusional state, 11 although disturbance in awareness is a more accurate description. The disturb ance of awareness tends to develop over hours to days, and typically fluctuates in the course of the day, often worsening in the evening.…”
Section: Deliriummentioning
confidence: 99%
“…The individual is, therefore, likely to have reduced orientation to their environment, and at times to oneself. This symptom has sometimes been referred to as 'reduced level of conscious ness' or confusional state, 11 although disturbance in awareness is a more accurate description. The disturb ance of awareness tends to develop over hours to days, and typically fluctuates in the course of the day, often worsening in the evening.…”
Section: Deliriummentioning
confidence: 99%
“…37 Factors that have been directly linked to misdiagnosis include atypical presentation, inexperience of the diagnosing clinician and a documented past psychiatric diagnosis. 35,38 In addition, womenwith misdiagnosed delirium are more commonly labelled asdepression, while men are more likely to receive an unspecified diagnosis. 35 …”
Section: Assessment In Clinical Practicementioning
confidence: 99%
“…A past psychiatric history has been shown in two studies to make delirium misdiagnosis more likely [10,15], though not in a palliative care setting [13]. In another study, Swigart et al did not find that an overall psychiatric diagnosis made misdiagnosis more likely, but specific diagnosesbipolar disorder and psychosisconferred nine times greater odds of misdiagnosis [3].…”
Section: Introductionmentioning
confidence: 95%
“…Otani et al found a low misdiagnosis rate of 8.1%, and related this to a relatively better understanding of psychiatric diagnosis by physicians in their hospital [14]. In contrast, Joshi et al found a much higher misdiagnosis rate of 73%, relating to their stringent classification as inaccurate in all cases where delirium was not mentioned specifically in the referral, even if delirium diagnosis was documented in the patient file [15]. In non-CLP settings, similar rates have been observed, with 61% of delirium misdiagnosed by the primary team prior to referral to a palliative care inpatient service [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation